Secondary home economics education and development of the comprehensive school in Thailand - Ketsripong, Somsong; Corpuz, Aurora Garcia (1972)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (M. Home Economics)--University of the Philippines, Diliman.
Keywords: Home economics--Study and teaching--Thailand.